Discovery of Dual Aβ/Tau Inhibitors and Evaluation of Their Therapeutic Effect on a Drosophila Model of Alzheimer's Disease - Gandini, Annachiara; Gonçalves, Ana Elisa; Strocchi, Silvia; Albertini, Claudia; Janočková, Jana; Tramarin, Anna; Grifoni, Daniela; Poeta, Eleonora; Soukup, Ondrej; Muñoz-Torrero, Diego; Monti, Barbara; Sabaté, Raimon; et al. (ACS chemical neuroscience, 2022)
Alzheimer's disease (AD), the most common type of dementia, currently represents an extremely challenging and unmet medical need worldwide. Amyloid-β (Aβ) and Tau proteins are prototypical AD hallmarks, as well as validated drug targets. Accumulating evidence now suggests that they synergistically contribute to disease pathogenesis. This could not only help explain negative results from anti-Aβ clinical trials but also indicate that therapies solely directed at one of them may have to be reconsidered. Based on this, herein, we describe the development of a focused library of 2,4-thiazolidinedione (TZD)-based bivalent derivatives as dual Aβ and Tau aggregation inhibitors. The aggregating activity of the 24 synthesized derivatives was tested in intact Escherichia coli cells overexpressing Aβ42 and Tau proteins. We then evaluated their neuronal toxicity and ability to cross the blood-brain barrier (BBB), together with the in vitro interaction with the two isolated proteins. Finally, the most promising (most active, nontoxic, and BBB-permeable) compounds 22 and 23 were tested in vivo, in a Drosophila melanogaster model of AD. The carbazole derivative 22 (20 μM) showed extremely encouraging results, being able to improve both the lifespan and the climbing abilities of Aβ42 expressing flies and generating a better outcome than doxycycline (50 μM). Moreover, 22 proved to be able to decrease Aβ42 aggregates in the brains of the flies. We conclude that bivalent small molecules based on 22 deserve further attention as hits for dual Aβ/Tau aggregation inhibition in AD.
Keywords: tau Proteins; bivalent ligands; Alzheimerova nemoc; proteiny tau; Drosophila; zvířata; Alzheimer Disease; β-amyloid; tau protein; protein aggregates; multitarget-directed ligands; aggregation inhibitors; Drosophila melanogaster; Animals